Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Mozambique - Map No. 3706 Rev. 6 - United Nations (United Nations, 2016)
Map Mozambique
Keywords: #Map / Mapa; G - Mozambique / Moçambique; L - english / inglês; demographics / demografia